PENGARUH KREDIBILITAS BERITA DAN JENIS BERITA PADA KONTEN INSRAGRAM @BATAMNEWSONLINE TERHADAP TINGKAT KEPERCAYAAN FOLLOWERS: PENDAHULUAN, KAJIAN TEORI, METODOLOGI PENELITIAN, HASIL DAN PEMBAHASAN, SIMPULAN, DAFTAR PUSTAKA - Puspitasari, Mia; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
The aim of this research is to analyze the influence of news credibility and the type of news on @batamnewsonline Instagram content on followers' level of trust. Information is considered very important nowadays, because information is needed by people to find information about the things they are looking for. The Instagram account @batamnewsonline spreads information especially in Batam City. Fulfilling information needs must have a message that has credibility from the media that conveys the message. The research method used is a quantitative method with descriptive research type. Based on the results obtained from data processing, it can be concluded that there is an influence of news credibility and the type of news on @batamnewsonline Instagram content on followers' trust with Fringing of 393,164 > Fubl 3,087 and a significance level of 0.000 which is 0.05. The big influence of news credibility and type of news on @batamnewsonline Instagram content on followers' trust is 88.7%.